Walk control of segmented multi-legged robot based on integrative control of legs and 2-DoF active intersegment joints. (17th October 2016) - Takahashi, Ryo; Inagaki, Shinkichi
Graphical Abstract: Abstract : This paper proposes a novel walk control method for multi-legged robots which have segmented bodies like a millipede. The segment of the robot which is addressed in this paper has a pair of legs which has 3 degrees of freedom (DoF) and 2-DoF active joint which connects the adjacent segmented body. The legs are controlled based on a decentralised control method, follow-the-contact point gait control, in which the legs contact on the contact-points where the forward legs have done. The joints between segments are controlled so as to make the bodies follow a desired trajectory. The legs and the intersegment joints are controlled with integrative and consistent manner thanks to local coordinate systems defined on each contact point. Finally, the proposed control method is verified via a robot simulator with physics engine.